Future past of punishment and actuality of an institution. Semiotic investigation of the representation of prisons in museums - Basso Fossali, Pierluigi; Thiburce, Julien (E|C, 2021)
In the context of the international traveling exhibition Prison, co-produced by the International Red Cross and Red Crescent Museum (Geneva), the Musée des Confluences (Lyon) and the Deutsches Hygiene-Museum (Dresden), a discourse on prisons is adressed to a wide audience. By mixing a corpus-based approach and a theoretical investigation, this article studies the enunciative strategies by which the museum is situated at the interface of the agenda of political institutions and the views of the public regarding the use of imprisonment as a legal and legitimate form of penalty, that is to say as an administrative management of “crimes and punishments”. Using audiovisual recordings of visits made in 2019 in Geneva and Lyon, we illustrate a semiotic analysis of the ways in which the spatial configuration of the Prison exhibition responds to a collective problem by addressing the individual engagements of audiences. We show how the meanings of the “museum” place and of the “prison” place are reciprocally transformed.